Assessment of the impact of fukushima nuclear wastewater discharge on the global economy based on GTAP. (1st September 2022) - Guo, Ji; Liu, Yanmin; Wu, Xianhua; Chen, Jihong
Abstract: The Japanese government intended to discharge more than 1.2 million tons of nuclear wastewater from the Fukushima Daiichi Nuclear Power Plant into the Pacific Ocean, arousing great attention from governments and people around the world. Using the Global Trade Analysis Project (GTAP) model, this article describes the impact of this event on the economic output of global countries and regions under different scenarios. The empirical results showed that: (1) The negative effects caused by nuclear wastewater discharge would reduce the GDP of affected areas, while other unaffected areas will increase. The total global social welfare loss could reach up to 219.8 billion U.S. dollars, accounting for 0.26% of global GDP in 2020. In addition, this negative impact would increase with the expansion of nuclear wastewater. (2) The discharge of nuclear wastewater would increase the trade imbalance between several regions and reduce the total production value of most countries or regions. This paper evaluated the economic losses caused by the discharge of nuclear wastewater on global countries or regions, and further revealed the negative consequences of the discharge of nuclear wastewater into the ocean. Graphical abstract: Image 1 Highlights: The GTAP model assessed the impact of Fukushima nuclear wastewater discharge on the global economy. The total global social welfare loss will reach up to 219.8 billion U.S. dollars. The nuclear wastewater discharge would reduce the GDP of affected areas, while other unaffected areas will increase.